Edge detection of the optic disc in retinal images based on identification of a round shape - Chaichana, T.; Sun, Zhonghua; Tangjitkusolmun, S.; Yoowattanna, S.; Sangworasil, M. (ISCIT, 2008)
This paper presents a novel method for identification of the position of the optic disc in retinal images. The method is based on the preliminary detection of the main edgedetection of retinal image. The segmentation optic disc is estimated as a circular area. We searched for areas of optic disc using Hough transform which detected several straight lines and approximated them as a circular line. The position of optic discwas identified as the center of the circle. An evaluation of the proposed procedure was performed using a set of 40 images from the DRIVE database, containing images from both healthy (33) and diseased (7) subjects. The optic disc position was correctly identified in 39 out of 40 images and the efficiency was 97.5 percent. The results illustrate that the proposed method can be used for pathological analysis of retinal images.